Gender differences in Taiwan's hypermarkets: Investigating shopping times and product categories. Issue 4 (12th September 2016) - Chang, Tsung-Sheng; Yeh, Hsiaoping
Abstract : Purpose: Hypermarkets face a very competitive environment, as their rivals also include traditional markets, convenient stores and supermarkets. In addition to offering innovative services, hypermarket managers must also pay attention to customer shopping patterns and behaviors in order to gain market share. The purpose of this paper is to posit that there will be significant differences between male and female hypermarket customers in terms of both shopping time and categories of goods purchased. Design/methodology/approach: To investigate actual shopping behaviors, this study observed customers in hypermarkets and recorded how long they spent shopping and what they purchased. Findings: The results of this study implied that gender is a key factor that affects both shopping time and the goods purchased in Taiwanese hypermarkets. The empirical findings also indicated that customers favor certain goods categories. Practical implications: The results of this study provide details of the differences between male and female hypermarket customers, with which managers can use to develop better marketing strategies. Originality/value: The purpose of this study is to show hypermarket retailers how gender differences affect customer behavior in this context. It also presents a consumer product categories list for hypermarkets, and this can be used as a reference for follow-up studies.